Chapter Seagrass detritus as marine macroinvertebrates attractor - Costa, Valentina (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Seagrass detritus is used as food, physical habitat and shelter. Using natural and artificial detritus, we tested if: 1) the colonisation was related to substrate availability rather than food 2) the assemblages were similar according to meadow structural complexity. A total of 11,270 invertebrates were identified. Neither the habitat complexity, nor the substrate type shown any effects on the colonisation, with both substrates acting as a faunal magnet. The detritus can be colonised by a rich and diverse community, highlighting its important role in maintaining the seagrass meadow biodiversity